2017
DOI: 10.6060/mhc171254z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Bioinorganic Systems Based on Nitrilium Derivatives of closo-Decaborate Anion and meso-Arylporphyrins with Pendant Amino Groups

Abstract: In this work we elaborated an approach to the synthesis of meso-arylporphyrin with pendant amino groups. This approach is based on the preliminary functionalization of 4-(4-bromobutyloxy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Then, the activated nitrilium group reacts with primary amine via a nucleophilic addition mechanism . This approach was successfully applied earlier for the synthesis of closo -decaborates with various substituents, including biologically active compounds . The reaction is conducted under mild conditions, providing high yield of the reaction product, which can easily be extracted from the reaction mixture.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the activated nitrilium group reacts with primary amine via a nucleophilic addition mechanism . This approach was successfully applied earlier for the synthesis of closo -decaborates with various substituents, including biologically active compounds . The reaction is conducted under mild conditions, providing high yield of the reaction product, which can easily be extracted from the reaction mixture.…”
Section: Resultsmentioning
confidence: 99%
“…The oxygenated derivatives of decaborate were used as precursors for producing polymers; treatment of isolated acyloxy and carboxonium derivatives of decaborate with an aqueous alcoholic solution of hydrazine yield the hydroxy derivatives [B 10 H 10‐n (OH) n ] 2− (n=1,2). This later can undergo condensation reactions at 60 °C, using Et 3 N as a base and dichloroorganosilane Si(R 2 )Cl 2 as cross‐linking agents [52] …”
Section: Substitution Derivatives In Closo‐derivatives Of [B10h10]2−mentioning
confidence: 99%
“…This later can undergo condensation reactions at 60 °C, using Et 3 N as a base and dichloroorganosilane Si(R 2 )Cl 2 as cross-linking agents. [52] Cyclic oxonium derivatives of decaborate are one of the most useful boron-oxygen compounds; the nucleophilic attack on oxonium beaks the carbon-oxygen bond and opens the oxonium cycle to produce a moiety separated from the decaborate by variety of spacers of determined hydrophilic/ lipophilic characters; [53] the ring-opening reaction of tetrahydrofuran (THF) or tetrahydropyran (THP) decaborate derivatives generates lipophilic spacers, whereas that of 1,4-dioxane derivatives gives hydrophilic one. For instance, Matveev et al elaborated the interaction between tetrahydrofuran, tetrahydropyran, and 1,4-dioxane derivatives of the [B 10 H 10 ] 2À anion and several amino acids such as glycine, cysteine, serine, and paminobenzoic acid.…”
Section: Closo-decaborate Derivatives With Boron-oxygen Bondsmentioning
confidence: 99%
“…It was previously shown that the addition of nucleophilic reagents of various natures to nitrile functional groups in anionic boron clusters can be considered as a convenient way of directed synthesis of their substituted derivatives [12][13][14][15][16][17][18][19][20][21][22][23][24], including those based on biologically active substances [6,25] and biomimetic systems [26,27]. It was found that the addition of tertbutyl esters of proteinogenic amino acids to nitrile derivatives of the closo-decaborate anion and their subsequent selective hydrolysis is a convenient method for the preparation of N-borylated peptides [28].…”
Section: Introductionmentioning
confidence: 99%